Legal Analysis Of The Impact Of Debtor Bankruptcy On Bank Credit Payment Performance (Research Study At Bri Batam Branch Office) - Ardyansyah Yacob; Erniyanti Erniyanti; Bachtiar Simatupang; Soerya Respationo (International Journal of Law, Crime and Justice, 2024)
Debtor bankruptcy is a critical issue that has a significant impact on the performance of credit payments in the banking sector, especially at the BRI Batam Branch Office. This study aims to analyze the juridical impact of debtors' bankruptcy on credit payment performance in BRI Batam, focusing on the direct influence of bankruptcy on bank liquidity, asset quality, and bank operations. In the legal context, debtor bankruptcy is regulated by Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, which provides a framework for the bankruptcy process and its settlement. The research method used is normative juridical, with a case approach to collect empirical data from the BRI Batam Branch Office. Data was collected through interviews with bank management, analysis of bankruptcy documents, and literature review related to bankruptcy laws and regulations. Data analysis was carried out in a descriptive analytical way to understand the legal implications and operational impact of debtor bankruptcy on credit payment performance.The results of the study show that debtor bankruptcy significantly affects the liquidity and credit payment performance in BRI Batam, with direct consequences in the form of an increase in bad loans and a decrease in interest income. Delays in legal proceedings and asset liquidation also add to the bank's operational burden. Based on these findings, it is recommended that BRI Batam should improve its credit risk monitoring system and adopt a more effective risk management strategy to anticipate and overcome potential bankruptcy. The government is expected to accelerate the legal process related to bankruptcy to minimize the negative impact on the banking sector and the economy as a whole.